PERAN KEPALA SEKOLAH DALAM MENINGKATKAN KOMPETENSI GURU PENDIDIKAN AGAMA ISLAM (di SMA Negeri 3 Kotawaringin Timur) - Salabi, Ahmad (LP2M IAIN Palangka Raya, 2014)
This study aimed to describe the principals role in improving the competence of Islamic Education Teachers in SMA Negeri 3 Sampit. This study used a qualitative descriptive approach, with information from the Principal, Vice Principal, Head of Administration, Islamic Religious Teacher, Student Council, and the School Committee. Data were collected through interviews, observation and documentation. The study found that in order to improve the competence of Islamic Education Teachers in SMA Negeri 3 Sampit, Principal maximize its role as educator, manager, administrator, supervisor, leader, innovator and motivator (EMASLIM), it resulted in increased competence paedagogik, personal competence, professional competence and social competence Islamic Education Teachers. While the efforts of Principal in improving the competence of Islamic Education Teachers include: (a) businesses in the school environment such as conducting in-house training (IHT), lifting the Islamic Education Teachers as Vice Principal, and involve Islamic Education Teachers in every activity school; and (b) venture beyond the school environment such as assigning Islamic Education Teachers participated in the training and upgrading as well as seminars, involving Islamic Education Teachers in the race outstanding teachers, and support the Islamic Education Teachers became Chairman of PAI MGMPs